Desarrollo del razonamiento lógico - matemático en la solución de operaciones básicas de los alumnos del quinto año " B" de la Unidad Educativa Mariscal Antonio José de Sucre en el período lectivo 2019-2020. - Pulloquinga Lasluisa, Héctor Fabián (2020)
In the present investigation the quantitative, approach was applied since it has a positivist paradigm, so its objective was to test the theories found in the place where this research was applied. The investigation of the project was accessible thanks to the existence of bibliographic information that was taken from several Research works, since the diagnosis and its application was carried out in the place under investigation reason why in the problem statement is detailed the need that children have to improve the development of mathematical logical reasoning in the solution of basic operations in the teaching-learning process through a proposal based on a specific objective; It began with the perceptual level because it favored exploring and describing everything all that is needed about the development of mathematical logical reasoning in the teaching-learning process, it was also apprehensive since it allowed us to collate and analyze the results obtained in this research, it was of comprehensive type since it will reveal everything that was discovered in its research, it will not be experimental because it did not transform existing theories, it was descriptive because it was oriented to the students’ progressive differences, the deductive method was applied since it was based on the observation of the problem it is to say the development of mathematical logical reasoning, followed by the problem, in what way does the logical mathematical reasoning affect the teaching-learning process, as deduction the given results of the empirical methods applied to the unit of study were taken into account and finally the proposal was applied as alternative of solution to the development of mathematical logical reasoning. In the present investigation the quantitative, approach was applied since it has a positivist paradigm, so its objective was to test the theories found in the place where this research was applied. The investigation of the project was accessible thanks to the existence of bibliographic information that was taken from several Research works, since the diagnosis and its application was carried out in the place under investigation reason why in the problem statement is detailed the need that children have to improve the development of mathematical logical reasoning in the solution of basic operations in the teaching-learning process through a proposal based on a specific objective; It began with the perceptual level because it favored exploring and describing everything all that is needed about the development of mathematical logical reasoning in the teaching-learning process, it was also apprehensive since it allowed us to collate and analyze the results obtained in this research, it was of comprehensive type since it will reveal everything that was discovered in its research, it will not be experimental because it did not transform existing theories, it was descriptive because it was oriented to the students’ progressive differences, the deductive method was applied since it was based on the observation of the problem it is to say the development of mathematical logical reasoning, followed by the problem, in what way does the logical mathematical reasoning affect the teaching-learning process, as deduction the given results of the empirical methods applied to the unit of study were taken into account and finally the proposal was applied as alternative of solution to the development of mathematical logical reasoning.